2015
DOI: 10.1681/asn.2013111202
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Autophagy Results in Mitochondrial Dysfunction and FSGS

Abstract: FSGS is a heterogeneous fibrosing disease of the kidney, the cause of which remains poorly understood. In most cases, there is no effective treatment to halt or retard progression to renal failure. Increasing evidence points to mitochondrial dysfunction and the generation of reactive oxygen species in the pathogenesis of CKD. Autophagy, a major intracellular lysosomal degradation system, performs homeostatic functions linked to metabolism and organelle turnover. We prevented normal autophagic pathways in nephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
125
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 149 publications
(128 citation statements)
references
References 35 publications
2
125
0
1
Order By: Relevance
“…These findings from human kidneys are preliminary, and additional work is needed before such long-reaching extrapolations can be made. It is curious, however, that podocyte-specific Atg5 deletion 8 did not result in the classic FSGS phenotype that is reported in the work by Kawakami et al 17 Although this could conceivably be explained by incomplete penetrance of podocyte-specific Atg5 deletion in the study by Hartleben et al, 8 the possibility that a coexisting tubule-based autophagy defect is also necessary to produce the full-blown picture must be investigated. How tubule defects might synergize with podocytopathy to produce the FSGS syndrome is something on which to speculate.…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…These findings from human kidneys are preliminary, and additional work is needed before such long-reaching extrapolations can be made. It is curious, however, that podocyte-specific Atg5 deletion 8 did not result in the classic FSGS phenotype that is reported in the work by Kawakami et al 17 Although this could conceivably be explained by incomplete penetrance of podocyte-specific Atg5 deletion in the study by Hartleben et al, 8 the possibility that a coexisting tubule-based autophagy defect is also necessary to produce the full-blown picture must be investigated. How tubule defects might synergize with podocytopathy to produce the FSGS syndrome is something on which to speculate.…”
mentioning
confidence: 97%
“…Hartleben et al 8 used podocyte-specific deletion of Atg5 and other interventions to show that podocyte integrity depends on intact autophagic flux; mice with autophagy deficiency in podocytes developed enhanced glomerulosclerosis as they aged (by 20-24 months). Although classic FSGS was not produced, these studies strongly supported autophagic failure as a possible cause for podocytopathy and glomerulosclerosis.A definitive study linking autophagy failure to FSGS is now reported by Kawakami et al 17 Kawakami et al 17 used Six2 promoter-driven Cre expression to delete Atg5 or -7 from all epithelium derived from metanephric mesenchyme. Atg5 deletion from tubules as well as podocytes produced a disease phenotype with uncanny resemblance to human FSGS by 2-4 months and advanced renal failure by 6 months.…”
mentioning
confidence: 99%
See 3 more Smart Citations